ǴALABALÍQ ASHÍQ ONLAYN-KURSLARDÍŃ (MOOC) INFORMACIYALÍQ-KOMMUNIKACIYALÍQ ÁHMIYETI HÁM KLASSIFIKACIYASÍ - Aimbetova, G.N.; Bekniyazova, N.D.; Yelmuratov, Q.Q. (SCIENCE and SOCIETY, 2024)
Higher educational institutions use a number of innovative methods and methodologies for distance learning of students and their independent work. This article analyzes the possibilities of massive open online courses using in systems that are implemented in mastering, a methodology has been developed for independent work through massive open online courses (MOOC, Massive open online courses) using innovative methods and technologies.